Prevalence of Periodontopathic Bacteria in Healthy Subjects and Adult Periodontitis Patients in China (Beijing) - Maeda, Nobuko; Okamoto, Masaaki (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 2003)
This study used the polymerase chain reaction to investigate the prevalence of 7 putative periodontopathic bacteria in 20 periodontally healthy subjects (33. 5±7. 0 years old) and 21 adult periodontitis patients 44. 8±12. 0 years old) in China Beijing). Subgingival specimens were collected with a paper point (from subgingival sites in healthy subjects (n= 20) and from healthy (n=16) and from diseased subgingival sites n= 21) in adult periodontitis patients. Porphyromonas gingivalis, Tannerella forsythensis, Treponema denticola, and Prevotella intermedia were frequently detected (from 85% to 95%) in the diseased sites of patients, and 3 species, Prevotella nigrescens, Prevotella pallens, and Actinobacillus actinomycetemcomitans, were moderately detected (from 24% to 33%). The distribution patterns of the 7 bacterial species were analyzed by Fisher's direct method. P. gingivalis, T. forsythensis, T. denticola, and P. intermedia showed a significantly similar pattern in the sampling sites (p<0. 0001), and they formed complex. P. nigrescens, P. Miens, and A. actinomycetemcomitans showed patterns that were partially similar to that of the above 4 species, and they formed four independent groups. In contrast to P. nigrescens, P. intermedia seemed to be an important etiogenic periodontopathogen, the same as P. gingivalis, T. forsythensis, and T. denticola. J Jpn Soc Periodontol, 45 : 163-170, 2003.